Will the Cranial Cruciate Ligament-Deficient Caprine Stifle Joint Develop Degenerative Joint Disease? - Thomson, L. A.; Houlton, J. E. F.; Allen, M.J.; Rushton, N. (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
Unilateral cranial cruciate ligament (CCL) resection was performed in six goats. Controls for this procedure included the contralateral (non-operated) joints and six normal joints. All CCL-deficient joints had a positive cranial drawer movement throughout the study, whereas all other joints were stable.None of the joints showed gross evidence of degenerative joint disease at necropsy 52 weeks after the operation. In addition, there were no statistically significant differences between either the frequency or severity of radiographic abnormalities in the two groups of joints.Despite long-term joint instability, degenerative joint disease did not develop in the CCL-deficient caprine stifle joint. When the goat is used as a model for anterior cruciate ligament-deficiency in man, the significance of any results should be assessed in the light of these findings.The long-term effects of experi-mentally induced cranial cruciate ligament (CCL) deficiency were studied in goats. All CCL-deficient joints had a positive cranial drawer movement, both immediately after surgery and at the end of the 52 week study. However, there was no evidence of cartilage or meniscal damage at postmortem examination, and stifle radiographs did not reveal evidence of degenerative joint disease.
Keywords: Anterior cruciate ligament; cranial cruciate ligament; degenerative joint disease; goat